2021
DOI: 10.3390/su132313311
|View full text |Cite
|
Sign up to set email alerts
|

Emotional State and Social Media Experience: A Pandemic Case Study

Abstract: The world has been experiencing an unprecedented global pandemic since December 2019. Lockdowns, restrictions in daily life, and social distancing characterize the new environment in which the world population finds itself, with minor variations depending on the country of residence. Television, social media, and other sources of information tend to influence and provide information about COVID-19 with varying tones. This study investigated the impact of alerts, news, and information about COVID-19 from social… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 59 publications
0
1
0
1
Order By: Relevance
“…A large number of scientific studies have been published that investigate the impact of the COVID-19 pandemic on emotions and sentiments. Previous studies have demonstrated that the COVID-19 pandemic has had a lasting impact on various aspects of human needs, including physiological needs, safety needs, and the need for care or affection (for example, see [65,66]). Among vulnerable groups, increased stress has been observed in individuals with chronic illnesses, while anxiety and sleep disorders have been noted in those with existing mental health conditions [67].…”
Section: Sentiment Analysis During Societal Crisesmentioning
confidence: 99%
“…A large number of scientific studies have been published that investigate the impact of the COVID-19 pandemic on emotions and sentiments. Previous studies have demonstrated that the COVID-19 pandemic has had a lasting impact on various aspects of human needs, including physiological needs, safety needs, and the need for care or affection (for example, see [65,66]). Among vulnerable groups, increased stress has been observed in individuals with chronic illnesses, while anxiety and sleep disorders have been noted in those with existing mental health conditions [67].…”
Section: Sentiment Analysis During Societal Crisesmentioning
confidence: 99%
“…A kormányzat a vélelmezhetően tudatos korlátos tájékoztatás helyett (Bán-Forgács 2021) transzparenciával, valódi társadalmi egyeztetéssel megteremthette, megerősíthette volna a társadalmi bizalmat, azonban az akarat mellett az idő is kevésnek bizonyult az ezt építő tevékenységek megvalósítására (Balázs 2021). A járványidőszak előrehaladtával a társadalmak világszerte egyre érzéketlenebbé váltak a koronavírussal kapcsolatos hírekre (Bitkina, Park 2021). Hazánkban e "természetes" folyamatok mellett az elégtelen tájékoztatás is kétségkívül hozzájárult a konteóhívők, vírusszkeptikusok és oltásellenesek (Brys 2021) táborának ütemes növekedéséhez, ami bizonyosan megnehezítette a járványkezelést is.…”
Section: A Helyi Társadalom Részvétele a Járványkezelésbenunclassified